Modeling for exponential growth and decay methodology in biometry using SAS syntax - Wan Ahmad, Wan Muhammad Amir bin; Mohamad Ghazali, Farah Muna; Mohd Noor, Nor Farid; Aleng, Nor Azlida (Universitas Ahmad Dahlan, 2021)
This paper provided an alternative method for exponential growth modeling as a regression analysis technique through the SAS algorithm. This alternative method is a combination technique (using nonlinear model bootstrap and fuzzy regression) for the small data set and gives the researcher an option to start the analysis, even if there is not enough data set. This method enhances the previous methodology with embedded bootstrapping and fuzzy technique to a nonlinear regression model. This principle aims to propose an alternative method of analysis with better results. In our case, we applied this principle to farm data and compared the results obtained by looking at the average width of the predicted interval.